An Assessment of Science Process Skills in Junior High School Education: Perspectives of Students and Teachers in Indonesia - Tawil, Muh. (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
This study aims to assess the understanding of science process skills (SPS) of science students and teachers in Indonesia: how is the picture of SPS understanding of student groups A, B, C, and D and teacher groups A, B, C, and D?; is there a significant difference in the average score of SPS understanding between student groups A, B, C, and D and teacher groups A, B, C, and D. The research method used is descriptive-inferential. Data collection uses SPS diagnostic tests. The research sample consisted of (580) students and (132) science teachers in Indonesia. The sampling technique used purposive sampling. The results of the study found that: the average score of students' SPS understanding was higher than that of teachers, there was no significant difference in the average score of SPS understanding between student groups A, B, C, and D and teacher groups A, B, C, and D; there is no significant difference in the average SPS understanding score between student groups A, B, and C. The descriptive analysis found that the average SPS understanding score of all student groups A, B, C and D was higher than all teacher groups A, B, C, and D. Factors of practical experience or access to SPS materials influenced this result; inferential statistical analysis found that there was no significant difference in the average SPS understanding score between all student groups A, B, C, and D and all teacher groups A, B, C, and D. Students and teachers still need to be trained in SPS with the application of project-based learning models or inquiry-based learning methods that directly involve SPS.